Metal-doped carbons from polyurea-crosslinked alginate aerogel beads. Issue 8 (24th March 2021) - Raptopoulos, Grigorios; Papastergiou, Maria; Chriti, Despoina; Effraimopoulou, Eleni; Čendak, Tomaž; Samartzis, Nikolaos; Mali, Gregor; Ioannides, Theophilos; Gurikov, Pavel; Smirnova, Irina; Paraskevopoulou, Patrina
Abstract : Polyurea-crosslinked alginate (X-M-alginate; M: Co, Ni, Cu) aerogels, prepared from the corresponding M-alginate wet-gels and the aromatic triisocyanate Desmodur RE, are precursors for metal- and nitrogen-doped carbon (X-M-C) aerogels. Abstract : Metal-doped polyurea-crosslinked alginate aerogel beads (X–M–alginate; M: Ca, Co, Ni, Cu) were prepared via the reaction of an aromatic triisocyanate (Desmodur RE) with the –OH groups on the surface of pre-formed M–alginate wet gels, and with adsorbed gelation water. The X–M–alginate aerogels consisted of 49–63% polyurea and contained 2–7% metal ions; they were fibrous macro/meso/microporous materials with porosities up to 94% v/v, and BET surface areas 245–486 m 2 g −1, comparable to those of native M–alginate aerogels (258–542 m 2 g −1 ). The pyrolysis of X–M–alginate aerogels (M: Co, Ni, Cu) at 800 °C yielded carbon aerogels (X–M–C; 33–37% yield) doped with the corresponding metal (as well as with Cu2 O in the case of X–Cu–C), with crystallite sizes of around 22 nm. The X–M–C aerogels retained the general fibrous morphology of their precursor (X–M–alginate) aerogels, and while X–Co–C and X–Ni–C appeared similar, the fibrous morphology of X–Cu–C was distinctly different, indicating an effect of the metal on the nanostructure of the corresponding carbon. The porosities of all X–M–C aerogels were in the range of 88–92% v/v, including macro-, meso- and micropores. Their BET surface areas were in the range of 426–541 m 2 g −1, of which 208–319 m 2 g −1 was allocated to micropores. In addition to the metals, XPS, Raman and FTIR analyses showed the presence of oxygen and nitrogen functionalities. Carbon in the X–M–C aerogels showed signs of stacking of graphene oxide sheets (14–15 nm), but also a low degree of graphitization and a large number of defects. This work provides a direct, inexpensive method for the preparation of fibrous metal-, oxygen- and nitrogen-doped carbon aerogels with potential for catalytic and electrochemical applications.